Phamacognostical and Phamaceutical Evaluation of Ikshvaku churna Lagenaria vulgaris Ser Fruit Pulp Powder - S, Patil (International Journal of Pharmaceutical & Biological Archive, 2012)
Phamacognostical and Phamaceutical Evaluation of Ikshvaku churna Lagenaria vulgaris Ser Fruit Pulp Powder